2006
DOI: 10.1002/cbf.1238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drugs affecting microtubular assembly on microtubules, phospholipid synthesis and physiological indices (signalling, growth, motility and phagocytosis) inTetrahymena pyriformis

Abstract: Structural changes of microtubules, incorporation of radioactively labelled components into phospholipids, cell motility, growth and phagocytosis were studied under the effect of four drugs affecting microtubular assembly: colchicine, nocodazole, vinblastine and taxol. Although the first three agents influence microtubules in the direction of depolymerization and the fourth stabilizes them, their effects on the structure of microtubules cannot be explained by this. Using confocal microscopy after an acetylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…Previous studies have shown that microtubules in Tetrahymena are present at the cytoproct, the site of egestion, although their function is poorly defined (Allen and Wolf, 1974, 1979; Kovacs and Csaba, 2006; Sugita et al , 2009). Our data suggest that while egestion was slower with colchicine (time did not have a significant effect, p = 0.3554) than without ( p = 0.0063), there was no significant difference in the rates ( p = 0.4840) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that microtubules in Tetrahymena are present at the cytoproct, the site of egestion, although their function is poorly defined (Allen and Wolf, 1974, 1979; Kovacs and Csaba, 2006; Sugita et al , 2009). Our data suggest that while egestion was slower with colchicine (time did not have a significant effect, p = 0.3554) than without ( p = 0.0063), there was no significant difference in the rates ( p = 0.4840) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated in our previous experiments that two types of cytoplasmic microtubule bands (longitudinal and transversal) react differently to drugs affecting microtubular structures (Kovács and Pintér, 2001;Kovács and Csaba, 2005a). E.g.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous experiments we obtained data on the connection of microtubular and signaling systems in Tetrahymena (Kovács and Pintér, 2001;Kovács et al, 2000), and on the effect of drugs affecting microtubular assembly to different kinds of microtubules in this unicellular organism (Kovács and Csaba, 2005a). The aim of the present study is to obtain additional data: 1./ on the alterations of different microtubular structures of Tetrahymena; 2./ on the alteration of posttranslational modification (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Microtubules are critical elements for a variety of fundamental cellular functions, including formation and maintenance of cell shape, transportation of vesicles and protein complexes, and regulation of motility and cell division [15]. Most of the anti-microtubule agents e.g., nocodazole, vinorelbine, colchicine and paclitaxel first bind with microtubules; thereby deregulate microtubule dynamics, activate mitotic spindle checkpoint and induces cell apoptosis [16][17][18]. It has been confirmed that suppression of microtubule dynamics and interference of microtubule polymerization or depolymerization, is an effective tool to block mitosis and kill tumor cells [19,20].…”
Section: Introductionmentioning
confidence: 99%